2009
DOI: 10.1252/jcej.08we173
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Crystallization of Lithium Carbonate Nanoparticles by Microwave Irradiation of Aqueous Solution Containing CO2 Microbubbles

Abstract: In this study, we used minute gas-liquid interfaces around CO 2 microbubbles activated by microwave irradiation as new reaction fields and developed a crystallization technique to produce lithium carbonate (Li 2 CO 3 ) nanoparticles. At the minute gas-liquid interfaces, nucleation occurs predominantly because of the formation of numerous local supersaturation regions at higher temperatures; hence, fine-sized Li 2 CO 3 particles with a narrow size distribution are crystallized, as the Li 2 CO 3 solubility decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 13 publications
(11 reference statements)
1
9
0
Order By: Relevance
“…Taborga et al [12] have investigated the effects of different additives on the size and morphology of Li 2 CO 3 crystals and have proposed that the presence of polyethylenimine (PEI), polyethylene glycol (PEG), and poly (4-styrenesulfonic acid) (P4SA) can increase the length of Li 2 CO 3 crystals. Matsumoto et al [13] developed a novel crystallization technique to produce Li 2 CO 3 nanoparticles using minute gas-liquid interfaces around CO 2 microbubbles activated by microwave irradiation. The results showed that with the formation of numerous local supersaturation regions at the minute gas-liquid interfaces, fine-sized Li 2 CO 3 particles with a narrow size distribution were crystallized due to the higher nucleation rate.…”
Section: Introductionmentioning
confidence: 99%
“…Taborga et al [12] have investigated the effects of different additives on the size and morphology of Li 2 CO 3 crystals and have proposed that the presence of polyethylenimine (PEI), polyethylene glycol (PEG), and poly (4-styrenesulfonic acid) (P4SA) can increase the length of Li 2 CO 3 crystals. Matsumoto et al [13] developed a novel crystallization technique to produce Li 2 CO 3 nanoparticles using minute gas-liquid interfaces around CO 2 microbubbles activated by microwave irradiation. The results showed that with the formation of numerous local supersaturation regions at the minute gas-liquid interfaces, fine-sized Li 2 CO 3 particles with a narrow size distribution were crystallized due to the higher nucleation rate.…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained in the two systems indicated that local supersaturation in the regions around the minute gas-liquid interfaces increased approximately twice compared with the supersaturation of the surrounding bulk solution, and the generation of numerous local supersaturation regions near the gas-liquid interfaces decreased the r C/CS necessary for the selective crystallisation of the metastable a-form and unstable b-form. Examination of the electrification of minute-bubbles was conducted by the zeta potential measurement to clarify the occurrence of interactions at the gas-liquid interfaces [13][14][15]. The zeta potential of the minutebubbles in water was negative, from À40 to À90 mV, at an average bubble diameter of 10-30 lm.…”
Section: Effects Of the Generation Rate Of Supersaturation In The Bulmentioning
confidence: 99%
“…In this study, a micron-scale bubble formation technique that enables the generation of local supersaturation in the regions around the gas-liquid interfaces was applied to the antisolvent crystallisation of glycine to control polymorphism. Minimising the bubble diameter in the gas-liquid systems helps achieve the following: (i) acceleration of mass transfer and reactive absorption with an increase in the gas-liquid interfacial area, (ii) an increase in the average residence time of the bubbles with a decrease in buoyancy, and (iii) the occurrence of interactions at the gas-liquid interface caused by electrification of minute-bubbles [13][14][15]. When minute-bubbles with the above properties are introduced into the antisolvent crystallisation of glycine, the local supersaturation at the minute gas-liquid interfaces increases due to the accumulation of glycine and antisolvent caused by the residence of minute-bubbles with surface potential in the liquid phase for a long period of time.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the previous studies, our experimental results indicated that not only increasing V MeOH but also bubble injection and minimizing bubble size led to the enhanced production of unstable ß-form caused by the inhibition of polymorphic transformation from ß-form to α-form. Investigation about the electric charge on the minutebubble surface to clarify the occurrence of interactions at the gas-liquid interfaces revealed that the zeta potential of minute-bubbles with d bbl of 10 -30 µm was negative value between -50 and -100 mV [6,7,9], and the presence of glycine and methanol led to the zeta potential approach to 0 mV [12]. These findings indicated that glycine and methanol concentrations increased locally in the vicinity area of minute gas-liquid interfaces.…”
Section: Comparison Of Antisolvent Crystallization Of Glycine Polymorphsmentioning
confidence: 99%
“…Minimizing bubble diameter in gas-liquid systems helps achieve the following: i) acceleration of mass transfer and reactive absorption with an increase in the gas-liquid interfacial area, ii) increase in the average residence time of the bubbles with a decrease in buoyancy, and iii) occurrence of interactions at the gas-liquid interface caused by electrification of minute-bubbles [6,7]. Because solute and antisolvent are accumulated near the gas-liquid interfaces by the residence of minute-bubbles with surface potential in the liquid phase for a long period of time, the production of a less stable polymorph and the shift in the overall solid-liquid equilibrium can be expected to occur.…”
Section: Introductionmentioning
confidence: 99%